Effect of Early Planting on Soybean Yield: 2022 Growing Season - E. Adee; S. Dooley; B. Pedreira (Kansas Agricultural Experiment Station Research Reports, 2023)
In an effort to increase soybean yield potential, early planting dates have been promoted as a management practice that can increase yield of soybeans. Early planting of soybeans can be a relative term, meaning late April/early May for some soybean producers in Kansas, but this definition of early planted soybeans is late March/early April. Theoretically, the earlier planting date could allow for more vegetative growth and interception of more light before blooming, increasing the yield potential. With the improvement of soybean seed treatments to protect seed when emergence is slowed due to cool and wet conditions, the early planting may be a viable option. The planting dates were late March, mid-late April, and May. At both irrigated locations, the highest yield was with the earlier planting date. At one location, the shorter season variety did not show a response to planting date.
Keywords: soybean; planting date; early planting